2012
DOI: 10.1186/1477-7819-10-219
|View full text |Cite
|
Sign up to set email alerts
|

The role of the 5-hydroxytryptamine pathway in reflux-induced esophageal mucosal injury in rats

Abstract: BackgroundDysfunction of the 5-hydroxytryptamine (5-HT) signaling pathway can lead to gastrointestinal motility and secretion abnormalities and to visceral hypersensitivity. The aim of this study is to investigate the role of 5-HT in reflux-induced esophageal mucosal injury.MethodsFifty 8-week-old male Sprague-Dawley (SD) rats were randomly divided into a gastroesophageal reflux (GER) model group (30 rats) and a sham surgery control group (20 rats). Four weeks after surgery, the esophageal mucosa was collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Liu et al ( 41 ) identified the expression of four subtypes of 5-HT 7 receptor throughout the rat gastrointestinal tract. Yang et al ( 42 ) concluded that a 5-HT signaling pathway disorder may be a major factor in the pathogenesis of gastroesophageal reflux and reflux esophagitis in experiments on rats.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al ( 41 ) identified the expression of four subtypes of 5-HT 7 receptor throughout the rat gastrointestinal tract. Yang et al ( 42 ) concluded that a 5-HT signaling pathway disorder may be a major factor in the pathogenesis of gastroesophageal reflux and reflux esophagitis in experiments on rats.…”
Section: Discussionmentioning
confidence: 99%
“…Acid‐induced esophagitis has been shown to cause significant hypomotility and peristaltic abnormalities in feline 47 and murine models 48 but Souza et al. observed that esophagitis in rats did not occur directly in response to acid contact.…”
Section: Resultsmentioning
confidence: 99%
“…6,7 It is known that an elevated serotonin level accompanies gastroesophageal reflux. 8 Serotonin has a stimulatory effect on the motor function of the esophagus. Activation of serotonin receptors can be performed by various doses of the neurotransmitter.…”
Section: Discussionmentioning
confidence: 99%